Effects of nutritional level of concentrate‐based diets on meat quality and expression levels of genes related to meat quality in Hainan black goats. (8th July 2014) - Wang, Dingfa; Zhou, Luli; Zhou, Hanlin; Hou, Guanyu; Shi, Liguang; Li, Mao; Huang, Xianzhou; Guan, Song
Abstract The present study investigated the effects of the nutritional levels of diets on meat quality and related gene expression in Hainan black goat. Twenty‐four goats were divided into six dietary treatments and were fed a concentrate‐based diet with two levels of crude protein (CP) (15% or 17%) and three levels of digestive energy (DE) (11.72, 12.55 or 13.39 MJ/kg DM) for 90 days. Goats fed the concentrate‐based diet with 17% CP had significantly (P < 0.05) higher average daily gains (ADG) and better feed conversion rates (FCR). The pH 24h value tended to decrease (P < 0.05) with increasing DE levels. The tenderness of Longissimus dorsi muscle (LD) and Semimembranosus muscle (SM) reduced with increasing CP levels (P < 0.05). With increasing DE levels, tenderness was increased (P < 0.05). The heart fatty acid‐binding protein (H‐FABP) mRNA expression levels in LD and SM increased with increasing DE levels (P < 0.05), but decreased with increasing CP levels (P < 0.05). The calpastatin (CAST) and μ‐calpain mRNA expressions levels in LD and SM were affected significantly (P < 0.05) by CP and DE levels in the diet. Therefore, the nutritional levels of diets affect meat quality and expression levels of genes associated with meat quality in Hainan black goats.